A teacher training for environmental education using projective techniques - Bonotto, Dalva Maria Bianchini (Paidéia (Ribeirão Preto), 2005)
The traditional model of teacher education has been reviewed, for analyzing the need of a greater participation of the teacher in this process, as professional and also as an individual. Under this view, the use of projective techniques may constitute a useful procedure to be used on the teacher education programs. They were used in an in-service Environmental Education program directed to elementary school teachers. In this paper, this experience is presented and the possibilities that this procedure may offers in terms of teacher education are discussed from analysis of reports held by the teachers attending the program.